Third Generation Cephalosporin Resistant Enterobacterales Infections in Hospitalized Horses and Donkeys: A Case-Case-Control Analysis - Anat Shnaiderman-Torban; Dror Marchaim; Shiri Navon-Venezia; Ori Lubrani; Yossi Paitan; Haya Arielly; Amir Steinman (MDPI AG, 2021)
In human medicine, infections caused by third-generation cephalosporin-resistant Enterobacterales (3GCRE) are associated with detrimental outcomes. In veterinary medicine, controlled epidemiological analyses are lacking. A matched case-case-control investigation (1:1:1 ratio) was conducted in a large veterinary hospital (2017-2019). In total, 29 infected horses and donkeys were matched to 29 animals with third-generation cephalosporin-susceptible Enterobacterales (3GCSE) infections, and 29 uninfected controls (overall n = 87). Despite multiple significant associations per bivariable analyses, the only independent predictor for 3GCRE infection was recent exposure to antibiotics (adjusted odds ratio (aOR) = 104, p < 0.001), but this was also an independent predictor for 3GCSE infection (aOR = 22, p < 0.001), though the correlation with 3GCRE was significantly stronger (aOR = 9.3, p = 0.04). In separated multivariable outcome models, 3GCRE infections were independently associated with reduced clinical cure rates (aOR = 6.84, p = 0.003) and with 90 days mortality (aOR = 3.6, p = 0.003). Klebsiella spp. were the most common 3GCRE (36%), and blaCTX-M-1 was the major β-lactamase (79%). Polyclonality and multiple sequence types were evident among all Enterobacterales (e.g., Klebsiella pneumoniae, Escherichia coli, Enterobacter cloacae). The study substantiates the significance of 3GCRE infections in equine medicine, and their independent detrimental impact on cure rates and mortality. Multiple Enterobacterales genera, subtypes, clones and mechanisms of resistance are prevalent among horses and donkeys with 3GCRE infections.